The Structure of the Political Instability in Iraq Based on David Easton’s Theory, From Post-Saddam to Post-ISIS - Younes Forouzan; Abdolreza Alishahi (رهیافتهای سیاسی و بین المللی)
Iraq should be considered as one of the major centers of the crisis, political unrest andideological confusion in the current era. From the Ba’ath impeachment period and SaddamHussein’s totalitarianism until the occupation of this country by the United States in 2003and eventually, ISIS’s security-political challenges in this country, Iraq have never beensuccessful in Development and the development of the political system. After ISIL’s relativedisintegration in Iraq, the issue that seems to be very important is the issue of reconstruction, development, integration and political development in this country. In this article, theauthors seek to answer this question by using the David Easton’s Political Instability theoryand the method of historical sociology )research method) try to answer this question howcan analyzed the pervasive political instability in Iraq Between 2003 )the fall of SaddamHussein) until 2018 (ISIS relative deterioration in Iraq)? The fndings of the article showsthat the Iraqi political system during this time can be likened to a political cycle. This cycleincludes broad changes in the political community, the occurrence of widespread changes inthe regime )rules), and ultimately, major changes in the authorities )the government). Therefore, widespread changes in this cycle caused the political instability in Iraq.